2011
DOI: 10.1007/s12070-011-0129-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hearing Loss in Tympanic Membrane Perforation

Abstract: To evaluate and analyse the hearing loss in tympanic membrane perforation based on size, site and duration of perforation. The material for this study was comprised of 100 patients of either sex and of age 15 years and above selected randomly. Size of tympanic membrane perforation was assessed under microscope using calibrated wire look. Patients were divided into three groups according to size; group I (0-9 mm(2)), Group II (9-30 mm(2)), Group III (≥ 30 mm(2)); according to site into anterior and posterior gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
42
4
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 7 publications
15
42
4
2
Order By: Relevance
“…A study conducted by Shiromany et al had patients in age range from 12 to 64 years and mean age was 26.7 ± 10.18 years (5). The mean age of patients in the present study was comparable with the other studies (6)(7)(8).Maximum patients i.e. 40% (24/60) were in age range of 18-20 years.…”
Section: Discussionsupporting
confidence: 89%
“…A study conducted by Shiromany et al had patients in age range from 12 to 64 years and mean age was 26.7 ± 10.18 years (5). The mean age of patients in the present study was comparable with the other studies (6)(7)(8).Maximum patients i.e. 40% (24/60) were in age range of 18-20 years.…”
Section: Discussionsupporting
confidence: 89%
“…The same findings were also shown by Pannu et al and Nepal et al in their respective studies who found perforation size to be the most important determinant of hearing loss. 13,14 This can be explained as the larger perforation size result in greater loss of middle ear and mastoid volume, a significant predictor of hearing loss and also decreases the phase effect due to the direct exposure of round window to the sound pressure. However in a contradictory study, Ribeiro et al evaluated 187 perforations and found no significant relationship between the size of tympanic membrane perforation and hearing loss at 500 Hz, 100Hz, 2000 Hz and 4000 Hz.…”
Section: Size Of Perforation With Hearing Lossmentioning
confidence: 99%
“…13 This can be explained on the basis that perforations over the posterior tympanic membrane expose the round window resulting in a sound pressure which diminishes cochlear response by a "phase cancellation effect". However in a contrasting report Ibekwe et al did a cross sectional prospective study on 62 consecutive adult patients with perforated tympanic membrane concluded that the location of tympanic membrane perforation has no effect on the degree of hearing loss in acute perforations, while it is significant in chronic ones.…”
Section: Site Of Perforation With Hearing Lossmentioning
confidence: 99%
“…8,9,11,12 We found that the hearing loss resulting from ML was more than that of non-MLs. same observations were made by Pannu and Kharadi et al .…”
Section: Discussionmentioning
confidence: 71%